Characterisation of the Impact of Genetic Variation of the Beclin1 Gene on Functionality of Autophagy Proteins - Herliana, Fadhilla Ika; Putra Siregar, Tegar Adriansyah (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Autophagy (from the Greek words auto, meaning alone, and phagi, meaning to eat) is an important pathway that regulates the homeostasis of an organism. When this balance is disturbed, pathological conditions can develop. Autophagy is divided into three types: (1) macroautophagy, (2) microautophagy, and (3) Chaperone-mediated autophagy (CMA). Modulator of the autophagy stage, (1) initiation, when starvation occurs, mTORC1 is inhibited and phosphorylated by AMPK, which results in activation of ULK1. Under normal conditions, cells use autophagy to recycle metabolites and nutrients from damaged organelles and misfolded proteins. The discovery of BECLIN1 was caused by the anti-apoptotic protein Bcl-2. Genetic variation is the difference in DNA sequence between individuals in a population. Autophagy works by removing damaged proteins and organelles during stress and ageing, playing an important role in regulating organism development, collaborating with the adaptive immune system, maintaining energy homeostasis, and maintaining protein and organelle quality control. This study aims to determine the impact of genetic variations in the BECLIN1 gene on the autophagy process. Methodology with a bioinformatics analysis approach using SIFT and PolyPhen-2 software. The results of the BECLIN1 gene prediction using SIFT software for Missense mutations showed that 31% of samples were Deleterious and 69% of samples were tolerated. Frameshift mutations found that 42.85% of samples experienced Deleterious and 57.14% of samples experienced Tolerated.